Population Aging in India: A Regional Comparison and Implications for Older Persons’ Welfare and Healthcare Infrastructure - Roy, Chandan; Kumar, Saurav; Kumar, Gaurav; Sati, Vishwambhar Prasad; Dhar, Murali (Journal of Population and Social Studies [JPSS], 2024)
Population aging is an inevitable consequence of demographic transitions, and declining fertility causes a rising burden of aging. The present study aims to project the aging index of various states nationwide up to 2031. In addition, the study estimates the year by which different states and union territories (UTs) will reach the Kerala levels index of aging (i.e., aged society). To conduct this study, data were gathered from the 2001 and 2011 Census of India. Using simple trend extrapolation techniques, we produced projections of aging indices up to 2031. Further, an index of aging of each state and union territory up to the level of Kerala state (i.e., aged society) was projected. The results showed that there will be a change in the age structure of the population from 2011 to 2031. There will be a 6% increase in the working-age group (15–59 years) and a 5% in the older population (60 years and above). However, there will be a decline of 11.2% in the children ages 0–14 years. The southern states and some states of north India, such as Punjab and Himachal Pradesh, are likely to attain Kerala’s level of aging index in the next few years. However, northern states are expected to take more years to achieve it. Therefore, there is a need to promote harmony between development and demographic change by expanding economic and social resources for older persons. The time has come to plan for the future burden of the older population across the country and arrange appropriate health facilities for them.